Cloning of a developmentally regulated element from alkalophilic Bacillus subtilis DNA. - Kudo, T (1985)
An alkalophilic Bacillus DNA bank cloned in an expression probe plasmid, pGR71, was screened for the presence of developmentally regulated genetic elements. A 508-base pair HindIII fragment isolated from this bank in plasmid pGR71-5 expressed plasmid-encoded chloramphenicol resistance only during the sporulation phase of a Bacillus subtilis host grown on Schaeffer medium. This developmentally regulated expression was altered in spo0E and spo0H mutants which had very low levels of chloramphenicol acetyltransferase activity relative to the wild type or other spo0 mutants. We determined the nucleotide sequence of the entire 508-base pair fragment and located the site of regulated transcription initiation by high-resolution S1 nuclease mapping of the in vivo transcript. The deduced promoter sequences upstream from this start site were 5'C-G-A-A-T-C-A-T-G-A3' at -10 and 5' A-G-G-A-A-T-C3' at -35. This transcript was not detected in spo0E or spo0H mutants, indicating that the products of these genes control developmentally regulated chloramphenicol acetyltransferase expression at the level of transcription.